Empowering Communities of Coffee Farmers via Risk Management and Coffee Berry Borer Control - Nasution, Anisah; Risnafitri, Hafizhah; Andriani , Dewi (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: Coffee farmers in Central Aceh face challenges with coffee berry borer pests, reducing yields and market value. Empowering the Musara Miko farmer group aims to address these issues through education and training in risk management and environmentally friendly pest control. Contribution: The purpose of this community service project is to raise awareness about coffee berry borer pest risk management and control. It is intended that by engaging in this activity, the community will be able to reduce the risk associated with producing coffee while simultaneously increasing output and improving quality. Method: This activity includes socialization, training, and practice. Risk management socialization activities are carried out to provide an understanding of risk management, training activities to make pest control tools using simple materials, then practice controlling coffee berry borer pests in the field. This activity involved 21 farmers as training participants. Results: This empowerment program showed an increase in knowledge about risk management and control of coffee berry borer pests by 71%. Conclusion: The program significantly improved farmers' ability to manage pests, enhancing productivity, quality, and market value, fostering sustainable coffee farming and economic welfare.